2019
DOI: 10.1002/bjs.11132
|View full text |Cite
|
Sign up to set email alerts
|

Predicting health status in the first year after trauma

Abstract: Background: Although mortality rates following major trauma are continuing to decline, a growing number of patients are experiencing long-term disability. The aim of this study was to identify factors associated with health status in the first year following trauma and develop prediction models based on a defined trauma population. Methods: The Brabant Injury Outcome Surveillance (BIOS) study was a multicentre prospective observational cohort study. Adult patients with traumatic injury were included from Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…Different results were found for Conscientiousness and Agreeableness. Surprisingly, except for high education in environment trajectory, no sociodemographic (e.g., female sex) and clinical characteristics were found as risk factors for impaired QOL, which is contrary with earlier research [12,15,17,18].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Different results were found for Conscientiousness and Agreeableness. Surprisingly, except for high education in environment trajectory, no sociodemographic (e.g., female sex) and clinical characteristics were found as risk factors for impaired QOL, which is contrary with earlier research [12,15,17,18].…”
Section: Discussioncontrasting
confidence: 99%
“…These disabilities and disorders were, together with sociodemographic (e.g., older age, female sex, low education) and clinical (e.g., higher injury severity score, hospital stay and ICU admission) characteristics, related to impaired health-related QOL (HRQOL) or health status (HS) [9,12,[14][15][16][17][18]. HRQOL is a limited definition of QOL, as it solely focuses on patients' subjective perceptions on health (i.e., physical and mental health), whereas HS refers to the extent of physical, psychological, and social functioning, but without taken patients' satisfaction with functioning into account [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming increasingly important to formally assess elderly patients for challenges to their functional status due to frailty 9–11 . Frailty is a measure of increased vulnerability and decreased physiological reserve to stressors, such as surgery, which impairs recovery and return to preoperative functional level 12,13 . It affects as many as 20 per cent of elderly patients, and may be associated with mortality, postoperative complications and longer hospital stay after surgery 4–7,14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies examined the prognostic factors for a lower health status in severely injured patients little is known about the differences between short-and long-term prognostic factors. De Munter et al (2019) [26] showed that pre-injury status is an important predictor of health status in the whole trauma population. However, it is unknown if these predictors are equal in the group of severely injured patients.…”
Section: Introductionmentioning
confidence: 99%